PERANCANGAN DESAIN MESIN VAKUM PEMISAH LIMBAH GERAM DENGAN OIL CUTTING MENGGUNAKAN AUTODESK INVENTOR : DESIGN OF VACUUM MACHINE FOR SEPARATING METAL SCRAP WASTE WITH OIL CUTTING USING AUTODESK INVENTOR - Yulia Puspa Dewi; Setiawan, Deny; Cahyono, Hiding; Mutiara Bahtiar, Ahmad Dony; Riswan Eko Wahyu Susanto (Program Studi Teknik Mesin PSDKU Polinema Kediri, 2023)
Metal scrap waste mixed with oil cutting can reduce the quality of the oil cutting itself, so it cannot be used directly. Meanwhile, the waste that is mixed with oil cannot be processed directly such as recycling / remelting. Cutting oil as a cooling material for the cutting process, so from here the recycle of cutting oil is needed, so a tool/machine is needed to separate the waste from the oil cutting. The research method used is design research which consists of planning machine elements and making machine designs. In the planning of machine elements, more emphasis is placed on the impler blade of the vacuum separator while the drawing uses Autodesk Inventor. From the results of the design and design of the